Adolescent experiences of living with a diagnosis of ADHD: a systematic review and thematic synthesis. Issue 2 (3rd April 2019) - Eccleston, Laura; Williams, James; Knowles, Sue; Soulsby, Laura
ABSTRACT: Seeking young people's perspectives is integral to delivering effective mental health care. This systematic review aimed to synthesise the qualitative research exploring the life experiences of young people diagnosed with ADHD. Four electronic databases (CINAHL, MEDLINE, PsycInfo and SCOPUS) were searched in February 2017 for peer-reviewed, qualitative English language studies exploring the perspectives of adolescents formally diagnosed with ADHD. Eleven studies were included and appraised for methodological quality and a thematic synthesis was undertaken. Participants' stories highlighted both positives and challenges within five analytical themes: Differing perspectives of the problem, Societal pressures, Sense of self, Feelings about medication, and Maturational shift from passive to active. The findings suggested that interpersonal conflict, stigma, and invalidation have a negative psychological impact upon young people's self-esteem and identity. Support strategies are needed to maximise adolescents' resilience, autonomy and abilities.